BEYOND HYPOTHESIS: AN UNSTRUCTURED INTERVIEW ON STORYTELLING TRAINING - Ira Mutiaraningrum; Meniwati Meniwati (IAIN Syekh Nurjati Cirebon, 2021)
Community empowerment in the border area has attracted considerable attention, including in terms of English Language learning. This study is a smaller part of a bigger project carried out in Temajuk Village, West Kalimantan, Indonesia.Â This study used unstructured interviews to explore what has neither been tested in the hypothesis nor questioned in the research problems. The unstructured interview has not really been put to use despite its ability in uncovering a wider range of topics of conversation. Thus this descriptive study seeks to examine participantsâ€™ thoughts after attending a six-meeting training of storytelling in English to tour guides in Temajuk Tourism Village. The findings revealed that participants appreciated the training given and are enthusiastic about attending more training. The pocketbook surprisingly is the most favorable way of teaching preferred by participants. This study also encourages the use of gradually increasing difficulty of method in teaching English for participants coming from different backgrounds of educations and ages. This study provides insights and input for future policies and programs for the empowerment of the border community.